Differences in mucin expression in the submandibular glands of rats during peridontitis induction - Nunuk Purwanti; Banun Kusumawardhani; Kwartarini Murdiastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Porphyromonas gingivalis (Pg) produces lipopolysacharide (LPS) which acts as a stimulator of inflammation in periodontal tissues. Periodontitis-induced apoptosis and vacuolation of the salivary gland, therefore, causes hyposalivation. Mucin secretion is produced by the submandibular gland under stimulation by the cholinergic and adrenergic receptors. Both forms of stimulation influence the volume of mucin secretion. Mucin saliva plays an important role in the early stages of Pg colonization in the oral cavity. On the other hand, it serves to protect against bacterial invasion. Purpose: The aim of this research was to identify differences in mucin expression in the submandibular gland during periodontitis induction. Methods: 32 male Wistar rats were assigned to either a sham periodontitis or a periodontitis group. The former group received a daily injection of a vehicle solution (n = 16), while members of the periodontitis induction group (n=16) were injected each day with 500 µL of Pg 108 into the mesial area of the upper molar. Mucin in the submandibular gland was analyzed at the 7th, 14th, 21th and 28th days after injection by means of periodic acid schiff (PAS) staining. Results: 28 days after injection mild gingivitis was developed in the periodontitis experiment group. Junctional epithelium (JE) thickness decreased gradually following the increase of PG injection periods (p<0.05). However, mucin expression increased prominently at 7th, 14th, and 21th days after injection and decreased on day 28th after PG injection. Mucin was expressed in the duct cells of the submandibular gland. Conclusion: The result of this study suggests that there are different levels of mucin expression in the submandibular gland during periodontitis induction.